The Implementation of Quran-Based Character Education to Prevent Bullying in Primary Schools - Hamdi Yusliani (Bansigom Na Publisher, 2025)
Bullying in primary schools has become a significant issue affecting the emotional and psychological well-being of children. This study explores the implementation of Quran-based character education as a proactive approach to preventing bullying among elementary school students. The research focuses on the integration of Quranic values, such as compassion, respect, and empathy, into the school curriculum and daily interactions among students. By employing qualitative methods, including interviews with educators, observations in classrooms, and surveys of students' perceptions, this study assesses the effectiveness of Quran-based character education in fostering a positive school climate. The findings indicate that incorporating Quranic teachings not only enhances students' moral values but also encourages a culture of kindness and respect, effectively reducing incidents of bullying. Furthermore, teachers reported improved student behavior and increased awareness of the impact of bullying on their peers. The study highlights the importance of collaboration among educators, parents, and the community in reinforcing these values both at school and at home. This research contributes to the growing body of literature on character education by demonstrating how spiritual and ethical teachings can play a crucial role in addressing social issues like bullying. The implementation of Quran-based character education serves as a promising strategy for creating a safer and more inclusive environment for all students in primary schools.